2017
DOI: 10.1039/c7nr02141k
|View full text |Cite
|
Sign up to set email alerts
|

Switchable changes in the conductance of single-walled carbon nanotube networks on exposure to water vapour

Abstract: We have discovered that wrapping single-walled carbon nanotubes (SWCNTs) with ionic surfactants induces a switch in the conductance-humidity behaviour of SWCNT networks. Residual cationic vs.anionic surfactant induces a respective increase or decrease in the measured conductance across the SWCNT networks when exposed to water vapour. The magnitude of this effect was found to be dependent on the thickness of the deposited SWCNT films. Previously, chemical sensors, field effect transistors (FETs) and transparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
1
6
1
Order By: Relevance
“…In this situation, most of the SWCNT surface would be covered with water molecules, and further water addition would elicit a small or no change in resistance. Our results differ from the results recently reported by Evans et al [26], who used SWCNTs in combination with anionic and cationic surfactants. It is also important to mention, that the SWCNT fabrication process and the film fabrication parameters (e.g., film thickness, type of SWCNTs, substrate type of surfactant) in ref.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…In this situation, most of the SWCNT surface would be covered with water molecules, and further water addition would elicit a small or no change in resistance. Our results differ from the results recently reported by Evans et al [26], who used SWCNTs in combination with anionic and cationic surfactants. It is also important to mention, that the SWCNT fabrication process and the film fabrication parameters (e.g., film thickness, type of SWCNTs, substrate type of surfactant) in ref.…”
Section: Resultscontrasting
confidence: 99%
“…It is also important to mention, that the SWCNT fabrication process and the film fabrication parameters (e.g., film thickness, type of SWCNTs, substrate type of surfactant) in ref. [26] differed from the parameters of the present work. Evans et al [26] reported a drop in conductance for semiconducting SWCNTs in the presence of water when they used anionic surfactants (e.g., sodium deoxycholate (DOC), sodium cholate (SC)) due to electrostatic interactions inducing an increase in the p-type nature of semiconducting SWCNTs.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations